"Can You Repeat That?" Teaching Active Listening in Management Education. (April 2018) - Spataro, Sandra E.; Bloch, Janel
Listening is a critical communication skill and therefore an essential element of management education. Active listening surpasses passive listening or simple hearing to establish a deeper connection between speaker and listener, as the listener gives the speaker full attention via inquiry, reflection, respect, and empathy. This article offers a method and tools for teaching active listening that can be implemented in online, hybrid, or face-to-face platforms. We begin by reviewing the great demand for listening skills, in light of how little time is spent on listening instruction compared with that on speaking instruction. We then present a set of learning materials and a procedure for using them that includes both pre- and posttests, multimedia learning materials, and exercises that enhance skill development. We follow the learning plan with analyses of both quantitative and qualitative data, showing support for the suggested method. These results fit with our personal experience of consistent success with the method across student levels (graduate and undergraduate) and platforms (online and face-to-face). Finally, we conclude with a discussion of the presentation and some implications for teaching listening in management education.